2009
DOI: 10.1016/j.socscimed.2009.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Are private physicians more likely to veto generic substitution of prescribed pharmaceuticals?

Abstract: Physicians'decisions whether or not to veto generic substitution were analyzed using a sample of 350,000 pharmaceutical prescriptions from the county of Västerbotten, Sweden. The primary purpose was to test if physicians working at private practices were more likely to oppose substitution than county-employed physicians working on salary. It was found that private physicians were 50-80% more likely to veto substitution. Also, the probability of a veto was found to be increased as patients'copayments decreased.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 17 publications
(17 reference statements)
0
36
1
Order By: Relevance
“…Inaccurate or insufficient knowledge about generics can cause ineffective and unsafe treatment. This situation can also lead to a high cost, contrary to expectations 2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Inaccurate or insufficient knowledge about generics can cause ineffective and unsafe treatment. This situation can also lead to a high cost, contrary to expectations 2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18…”
Section: Introductionmentioning
confidence: 87%
“…Both in developed and developing countries, health insurance agencies, health authorities and governments have suffered from pharmaceutical expenditures that has risen rapidly especially in the last two decades 2,3,4,5,10,11,12,13,14,15. Substitution of generics for brand-name might be an alternative way to reduce drug expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…Once included in the pharmaceutical benefits scheme by LFN, applications for price increases are required to price of the more expensive prescribed drug. Physicians only prohibited substitution for a few percent of the prescriptions (Granlund, 2009). include motivations for the price increase as well as information about the prices and treatment costs of comparable drugs (RFFS 1996:31, LFNFS 2003. If the requested price is the same as or less than the price of the most expensive substitutable product in the reference group, no motivation is needed and the price increase is always accepted (LFNAR 2006:1).…”
Section: Price Setting and Distributionmentioning
confidence: 99%
“…This indicates that the reform has increased the probability that pharmacies inform consumers about their right to buy other substitutes than the prescribed product or the cheapest available substitute. This paper relates to many studies on determinants of choices between medically equivalent pharmaceuticals (Leibowitz, Manning, and Newhouse 1985;Hellerstein 1998;Coscelli 2000;Mott and Cline 2002;Granlund 2009) even though these studies have focused on the choice between brand name and generics and primarily analyzed the role of physicians. Using survey data on 3,000 prescriptions from pharmacies in a Midwestern state, Mott and Cline (2002), however, found that pharmacy random effects accounted for 43% of the variation in the occurrence of generic substitution.…”
Section: Introductionmentioning
confidence: 99%